Active policies to promote active aging and address demographic challenges in Bulgaria - T. Vazova; Y. Stasiuk (Medičnì Perspektivi, 2025)
The article explores the concept of active aging in Bulgaria, emphasizing the economic, social, and health benefits of implementing policies aimed at older adults. In light of the rapid population aging, Bulgaria faces significant demographic challenges impacting its economic, social, and health systems. The primary objective of the research is to analyze the strategic framework and active aging policies at both national and regional levels, focusing on their effects on the quality of life, health status, and social integration of the elderly. This study uses a mixed methods approach integrating both quantitative and qualitative analysis to assess the economic and social impact of active aging policies in Bulgaria. This approach combines quantitative data that provide objective measurements of current status with qualitative analyzes that provide an in-depth understanding of the context and impact of existing programs. Through this approach, the research aims to provide a basis for formulating specific and effective recommendations to improve policies and programs in the field of active aging and healthy living of the elderly. This multi-layered approach will provide a basis for future research and policies aimed at improving the quality of life of older people, emphasizing the importance of active aging and healthy lifestyles in the context of dynamically changing social and economic conditions in Bulgaria. Active aging is linked to numerous benefits, such as improved health outcomes, increased social engagement, reduced poverty, and enhanced economic productivity. By fostering an active lifestyle and improving access to health and social services, the pressure on Bulgaria's healthcare system is alleviated. However, challenges persist, notably insufficient coordination among institutions and a lack of integrated policies. The article concludes with specific recommendations for enhancing existing programs, including the establishment of a central coordinating body for active aging policies, ensuring sustainable funding for health and social services, and implementing innovative strategies such as digital learning for promoting healthy lifestyles and chronic disease prevention. These measures aim to enhance the socio-economic and health conditions of the elderly in Bulgaria while supporting overall economic growth.